Characteristics of Youth and Young Adults at Risk of Homelessness in the U.S. - Melissa A. Kull; Susan Frankel; Samantha Gills (Youth)
In this study, we identified differences in characteristics and circumstances, main presenting problems, and types of referrals received among young people who were in crisis, at imminent risk of homelessness, or currently homeless. This study draws on data from 11,566 young people who contacted the National Runaway Safeline (NRS) through the National Communication System (NCS), a federal program for young people at risk or experiencing homelessness in the U.S. and those who care for them. Frontline staff collect information directly from young people during crisis intervention engagement through the NRS. We used multinomial logistic regression analyses to predict membership in each of the homelessness risk categories and logistic regression analyses to predict the type of service referrals young people received. Results revealed that young people’s circumstances and presenting problems were associated with homelessness risk category membership, which in turn was linked with the types of service referrals young people received. This study illuminates valuable opportunities for targeting prevention opportunities to the specific needs of young people with varying levels of homelessness risk.